Pemberdayaan Masyarakat Desa Tongke-Tongke melalui Pemetaan Potensi dan Pemanfaatan Sumber Daya Lokal sebagai Pengembangan Desa Wisata - Murdiani Sukarana; Muh Kasim; Sudarmi (Panrannuangku Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to develop Tongke-Tongke Tourism Village in Sinjai Regency through potential mapping and the utilization of local natural resources. The main problems identified include limited accessibility and the suboptimal use of local resources such as palm sugar and coffee. The implementation method employed a participatory approach involving observation, focus group discussions (FGD), and hands-on training in processing coffee drinks with palm sugar. The results show an improvement in community understanding and skills in managing tourism potential, as well as emerging initiatives to develop local beverage businesses. This activity contributes to enhancing community capacity in sustainable village tourism management and strengthens the local economy through innovation based on locally sourced natural resources.